Appearance Reveals Music Preferences. (December 2022) - Tian, Laura; Alaei, Ravin; Rule, Nicholas O.
Disclosing idiosyncratic preferences can help to broker new social interactions. For instance, strangers exchange music preferences to signal their identities, values, and preferences. Recognizing that people's physical appearances guide their decisions about social engagement, we examined whether cues to people's music preferences in their physical appearance and expressive poses help to guide social interaction. We found that perceivers could detect targets' music preferences from photos of their bodies, heads, faces, eyes, and mouths (but not hair) and that the targets' apparent traits (e.g., submissiveness, neatness) undergirded these judgments. Perceivers also desired to meet individuals who appeared to match their music preferences versus those who did not. Music preferences therefore seem to manifest in appearance, regulating interest in others and suggesting that one's identity redundantly emerges across different types of cues. People may thus infer others' music preferences to identify candidates for social bonding.